Pemberdayaan Kader Posyandu melalui Sistem Informasi Gizi Komplementer untuk Peningkatan Kualitas MP-ASI - Meilita Dwi Paundrianagari; Chindy Amir; Marzuki Pilliang (Nindikayla Institute, 2025)
Indonesia still faces serious challenges related to nutrition problems in children, with the prevalence of stunting still high. Quality Complementary Feeding of Breast Milk (MP-ASI) plays a crucial role in supporting the optimal growth and development of toddlers. However, many mothers have difficulty in providing MP-ASI that meets nutritional standards, due to a lack of knowledge, limited resources, and limited access to information. Posyandu cadres as the spearhead of public health services have a central role in providing education and assistance to mothers under five. However, they often face limited knowledge and access to adequate information related to nutrition. This research aims to empower Posyandu cadres through the implementation of a complementary nutrition information system. The methods used include intensive training, mentoring, and the development of a web-based information system that is easy to access and use. The results of the study showed a significant increase in the knowledge and skills of cadres about nutrition, as well as an improvement in the quality of MP-ASI provided by mothers under five. Information systems have proven to be effective in facilitating knowledge transfer, facilitating access to information, and improving the efficiency of cadres' work. The conclusion of this study is that the empowerment of Posyandu cadres through a complementary nutrition information system is an effective strategy to improve the quality of MP-ASI and ultimately contribute to reducing stunting and improving the quality of human resources in Indonesia. Recommendations include expanding the implementation of information systems in various regions, improving training and mentoring of cadres, and developing more comprehensive information content.